Posted by **bobpursley** on Sunday, December 3, 2006 at 11:06am.

I find it curious here:

a - b=2 in this case,

rationalize by multplying both sides by a+b, getting

a-b=2

a^2-b^2=2(a+b)

2x+3-x+2=2(a+b)

(x+5)/2 = a+b

now add the original equation..

2= a-b

or 2a= 2+ x/2 + 5/2

4sqrt(2x+3)= x+9

square both sides..

16(2x+3)= x^2+18x + 81

x^2-14x+33=0

(x-3)(x-11)=0

square root sign 2x+3 - square root sign x-2 = 2. And the instructions are to solve the equation.

## Answer this Question

## Related Questions

- algebra--distributive - how would you do this prob. negative4-(5y+6) = negative ...
- science - rearrange this equation 2 make x the subect. 6y = 9 - 3x so first i ...
- algebra - I need a step by step explanation on how to add these two equations 2x...
- Pre Cal.--Check my work? - Solve the system of equations: x - y - z = 2; x + 2y...
- Pre Algebra - Here is another one I need help with. -5x+20=-60 ( remember it is ...
- Math - 4(j)-7=9 Add 7 to both sides of the equation and you get 4 j = 16 Now ...
- Algebra - Can you explain to me how to solve this equation? 2/3x-9=1/3 1/3=.33 ...
- Algebra - 89. Solve for x in the equation: 6/7x - 6 = -2 I posted this before, ...
- algebra - could someone check my answers to these few questions? "What is the ...
- ALGEBRA - I believe this answer to be correct. Just need to know. -13<= 4x-2&...